Miles-Ezzell's WACC Approach Yields Arbitrage - Andreas Löffler (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2002)
A simple counterexample shows the the widely used WACC approach to value leverage firms developed by Miles and Ezzell can create an arbitrage opportunity. The only consequence to be drawn is that their WACC approach cannot be applied under the circumstances assumed by Miles and Ezzell.
Keywords: 330; WACC; leverage ratio; tax shield